ANALISIS PENGARUH PDB PERKAPITA, NILAI TUKAR RUPIAH, BUNGA DEPOSITO, TINGKAT INFLASI TERHADAP HARGA SAHAM ( STUDI KASUS PADA BURSA EFEK INDONESIA SEKTOR PERBANKAN PERIODE TAHUN 2008-2013 ) - MARLINI, WENNY (Politeknik Dharma Patria Kebumen, 2017)
Investors will usually do stock analysis in an effort to obtain optimal stock returns, but that would be that of the stock price. Rational factors that influence the decision of potential investors to buy stocks, generally associated with something called fundamentals. Where changes in inflation, interest rates, exchange rates and economic petumbuhan (GDP per capita) will respond directly by the capital market, so that these factors has the potential to increase or decrease the stock return. This research was conducted by using secondary data obtained from financial statements of Bank Indonesia, BPS, Indonesia Stock Exchange, and the financial statements of Bank Rakyat Indonesia. The study was limited from 2008 to 2013, namely the banking sector and the research conducted on only one major bank, Bank Rakyat Indonesia. Data analysis using multiple linear regression analysis that has been tested prerequisites including normality test, multicollinearity, and heterokedastisitas.After the analysis is obtained simultaneously, GDP per capita, Exchange Rate, Deposit Interest, Inflation has a significant influence on stock price. However, GDP per capita is only partially be having a significant effect on stock prices, while the other is Rupiah Exchange, Deposit Interest, Inflation does not affect significantly secra, so these macroeconomic variables only a small portion that would affect only when together - together or simultaneously.